Spirited Diasporas : Personal Narratives and Global Futures of Afro-Atlantic Religions - Otero, Solimar; Tsang, Martin (Book collections on Project MUSE., 2023)
"First-person accounts that show the expanding demographics of African-descended religions In this focused portrayal of global dispersal and spiritual sojourning, Martin Tsang draws together first-person accounts of the evolving Afro-Atlantic religious landscape. Spirited Diasporas offers a glimpse into the frequently misunderstood religions of Afro-Cuban LukumiÌ, Haitian Vodou, and Brazilian CandombleÌ, adding to the growing research on the transnational yet personal nature of African diasporic religions. In these accounts, practitioners from many origins illustrate the work and commitment they undertook to learn and become initiated in these traditions. They reveal in the process a variety of experiences that are not often documented. Their perspectives also show the expanding contemporary demographics of African-descended religions, many of whose members identify as LGBTQ or are part of other minoritized populations, and they counter inaccurate and often racialized portrayals of these religions as being anti-modern and geographically limited. Through the voices of the professionals, scholars, and activists gathered here, readers will appreciate the purpose and belonging to be found in the far-reaching communities of these Latin American and Caribbean spiritualities. As the seekers in these stories discover and come home to their new religious families, Spirited Diasporas displays the relevance and generative power of these traditions."--